A Single Analysis of Elements in Groundwater (ng L-1 to g L-1) by DRC ICP-MS Using Extended Dynamic Range Techniques - Zhang, Jiangyi; Guo, Wei; Li, Guomin (Asian Journal of Chemistry, 2015)
Simultaneous determination of elements in groundwater (ng L-1 to g L-1) in single analysis by DRC ICP-MS was developed. The technique of extended dynamic range based on DRC could be able to detune the signal response of selective elements to enable incorporation of high concentration elements (outside of the ion detector' dynamic range to 1e9 cps) into a single analysis without affecting signal response of other trace elements. The signal sensitivity of high concentration element (i.e., K, Na, Ca, Mg and Fe) was suppressed easily by adjusting the voltage parameters of DRC quadrupole (RPa) and the groundwater samples could be online diluted any multiples (i.e., from one time to million times) according to the actual need. In order to eliminate mass spectral interferences (i.e., 40Ar35Cl+, 40Ar40Ar+, 12C40Ar+, 44Ca16O+, 23Na40Ar+, 25Mg38Ar+ and 26Mg40Ar+), the operational conditions of the DRC, working with CH4 as reaction gas, were optimized for 75As, 80Se, 52Cr, 60Ni, 63Cu and 66Zn. The analytical results of a reference material CASS-5 were in good agreement with the certified values. Reliability of the data was also tested by comparing the results for 29 groundwater samples with those determined by ICP-OES and good agreement was obtained for the high concentration elements. As the routine method in our laboratory, the satisfactory results indicate that it has great potential for the determination of low and high concentration level elements by one single analysis in various samples.